Konsep Pendidikan Profetik Sebagai Pilar Humanisme - Wahyu Ningsih; Sufitriyani Sufitriyani; Siti Diyaus Sobah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Prophetic education refers to the teachings and example of Muhammad Shallallahu 'Alaihi wa Sallam as the last Prophet and messenger of Allah Subhanahu wa Ta'ala. This concept emphasizes the importance of integrating humanist values ​​in education. Prophetic education as a pillar of humanism teaches individuals to develop a deep understanding of human values, empathy and social justice. In practice, prophetic education encourages individuals to develop character with noble character and good behavior. Education is not only about academic knowledge but also about forming a good and responsible personality. Prophetic education teaches individuals to become human beings who contribute positively to society. By applying the concept of prophetic education as a pillar of humanism, it can be hoped that individuals will become humans who are more aware of human values, empathy and social justice. This will help in building a harmonious society; fair and prosperous.